(untitled) (Heritage, 2020)
The role of the noble families in Medieval Serbia, as in other states of that time, was of great importance—their social status affected the character and the success of the statehood. They represented social elite, which influenced the development of various processes, one of them being migration. The migration process could be voluntary or involuntary, but it shadowed inner colonisation as well as the conquest of new territories. It determined the establishment of the governing structures in the newly acquired territories, as well as their integration into the state. Bearing in mind that many wars were waged during the Middle Ages—hence the constant redrawing of the borders—it is not surprising that migration was an ongoing process of various intensity and direction. Both the dependent population and the nobles took part in the process. However, following the migration flow of the noble families through history is much easier. The great expansion of the Serbian territory started during the reign of King Milutin and ended with the death of the Tsar Dušan (1282-1355), whose reign was especially marked by great conquests and extensive migrations. Though conquests are mainly attributed to rulers, the noble families often initiated them. This is confirmed in the historical sources and the research literature, which cites the growing dissatisfaction of the nobles and their desire for further conquest as the main reasons for the change in the Serbian throne after the great victory at Velbazhd in 1330. Such views are further substantiated by the early years of the reign of Stefan Dušan when significant territories in Macedonia were annexed. According to several sources, the main driver of change was the number of noble families close and directly subordinate to the young king. It is well known that Dušan inherited the governance of Zeta and western Serbia from his father in 1322. He managed those territories during the whole reign of Stefan Uroš III (Stefan of Dečani). The previous contention that the nobles drove the change in the throne is also validated by the relocation of the noble families to the newly annexed regions. A certain number of high born families originated from the western Serbian areas which is proved by the primary historical souorces, while other families are loosely associated to the area by stories and legends. Neither is simple to confirm. Some of those nobles from the western Serbia are: the Braković familiy, the Mrnjavčević family, the Great Duke Nikola Stanjević, Ostoja Rajaković Ugarčić, Radoslav Hlapen, Nikola Bagaš, Andrija Gropa, Lord Žarko, and most probably Caesar Preljub, among others. They all received inheritance and governance of various territories as a reward for their loyalty and accomplishments, which can be traced back through their titles. Namely, military titles indicate that the person gained their status owning to their warrior abilities.